Urban Mahabharata: Health care, ordinary, traditional, and contemporary ethics (Medicine Anthropology Theory, 2017)
In Affliction: Health, Disease, Poverty (Fordham, 2015), we listen with Das to ordinary ethics in challenged lives of poverty, illness, and family relations; and in three registers of (a) advocacy, (b) moral engagement, and (c) acknowledgement of the inherent uncertainties in the very fabric of living these lives, including hers and ours. In this article, I take up the text of Affliction, and comment on moral engagements and sparks of references to the Mahabharata and other traditional, especially Muslim, modes of ethical thought. This commentary can be read as what in Islamic scholarship often are called ‘hashiye’, marginal notes on the main text. I conclude by discussing a mosaic of coverage and gaps in the contemporary ethics of Indian health care and its anthropologies.